Implementasi Metode Group Investigation (GI) dan Mind Mapping dalam Pembelajaran Matematika terhadap Prestasi Belajar ditinjau dari Kemampuan Penalaran Siswa Kelas VIII di SMP Muhammadiyah 7 Surakarta Tahun Ajaran 2016/2017 - Dianasari, Zulfa; , Rita P. Khotimah, S.Si., M.Sc (2017)
The research purposed to examine: (1) the effect of methods Group Investigation (GI) and Mind Mapping toward mathematics achievement, (2) the effect of reasoning ability students' toward mathematics achievement, (3) the effects of the interaction between learning methods of Group Investigation (GI) and Mind Mapping toward mathematics achievement. The type of the research is a quantitative with experimental design. Population of the research was the eighth grade students of Junior High School in Muhammadiyah 7 Surakarta academic year 2016/2017. The sample was class eighth D and eighth G. The technique of sampling is sampling techniques. Methods of collection data is documentation and test. Mechanical data analysis using statistical techniques to test two-way analysis of variance. The result of this research show that: (1) There is an effect method of Group Investigation and Mind Mapping toward mathematics achievement with FA> Ftable it's 10.3248> 4.314, (2) There is an effect reasoning ability of students to learn mathematics achievement with FB> Ftable it's 11, 9206> 3,284 (3) There is no interaction effect between teaching methods and reasoning skills at the level of high, medium and low on mathematics learning achievement of students, with the result of the test statistic FAB <Ftabel, it's 0.0870 <3.284. Keywords: Group Investigation, Mind Mapping, reasoning ability, academic achievement.